Retroperitoneal multiple giant liposarcoma: a case report - Hou, Jiaxin; Yang, Qingqiang (Frontiers in Surgery, 2025)
The retroperitoneal anatomical space is located below the diaphragm and above the pelvic diaphragm, in the potential space between the posterior parietal peritoneum and the abdominal transverse fascia. Retroperitoneal liposarcoma is a common tumor in this region of the body. It typically presents no obvious clinical symptoms in the early stage due to the capaciousness of the area. Usually, however, an increase in tumor volume causes compression of the surrounding tissues and organs, such as intestinal obstruction and urinary obstruction, which leads to prominent symptoms. Primary giant retroperitoneal liposarcoma is a rare clinical entity. A comprehensive review of the literature reveals only a limited number of documented cases, with heterogeneity in their presentation, management, and outcomes. This report presents a case of multiple giant retroperitoneal liposarcomas successfully managed with multivisceral resection achieving R0 status. This case highlights the surgical challenges and feasibility of complete resection even in massive and multifocal tumors.